A família e os projetos sociais voltados para jovens: impacto e participação - Feijó, Marianne Ramos (2008)
The focus of the present work is the study of social projects aimed for youngsters and the impact of such projects on their families. Through this study we tried to understand the relevance of such projects to increase the possibilities of relationships, autonomy and the role of the involved parties. Through interviews, we have surveyed professionals, youngsters and their families, the changes that occurred in the participants, their families and their social relations during the study period. For such purpose, we employed the new paradigm of a systemic cybernetic focus, with emphasis in relationships and interactions. The reality is seen as built according to a social constructionistic viewpoint (GRANDESSO, 2000), where one tries to understand subjects as authors who influence and who are simultaneously influenced by their environment; subjects who build their social experience through the language; who affect and are affected by their culture (MOTA and CIURANA, 2002). It was also based on systemic studies on the importance of the social network on the health of individuals and in the development of a human being, his/her family and community (SLUZKI, 1997) as well as in proposals for social projects. A qualitative study has been developed with the analysis and interpretation of seventeen interviews, made with seven professionals who worked at three social projects and who previously worked in over ten projects in the fields of sports, culture, citizenship, assisted freedom, computing and tutorship; five youngsters and five family members of those teenagers participated in the study. Trough the interviews we identified the need to bring families closer to those respondents who participate in the social projects. Such family participation is important for the families and the youngsters involved and also helps to promote the strengthening of social networks, for these stronger social networks may give support to lower income families, who in turn may increase their social participation, implying in the reduction of misery and social inequities in the country. However, working with these families presented several difficulties such as: funds shortage, lack of preparation on part of the professionals in charge of carrying out activities where families are involved and hardships in getting access to these families in the few activities geared towards them. Work was the most frequently mentioned as the pressing need of the respondents, and it stands out as a factor related to the vulnerability and suffering of less privileged populations